Analysis of the verbal lexical frequencies of university essays by students advised in the Writing Clinic of the School of Psychology of the UASLP, Mexico - Pérez, Marco (2023)
This paper aims to describe the frequency of occurrence of verbal words, in 68 productions written by university students at the School of Psychology of the Universidad Autónoma de San Luis Potosí, México. The students attended counseling sessions on academic writing before the COVID-19 pandemic period. The methodology used was quantitative-contrastive. The data analysis was carried out by applying the AntConc, a free access program. The word position (Rank), the frequency of repetition (Freq) and the words themselves (types and tokens) were obtained. A total of 350 verbs were identified and the 10 most frequent (38 % in total) were taken and contrasted with the CREA corpus of the RAE and the corpus of adult, children, and journalistic texts of Moreno and Guirao (2008). The results show that there is no significant variation between the contrasted corpora. Students frequently use attributive and auxiliary verbs in their text productions. The results discussed in this paper highlight the need to include the use of more complex verbs in writing curricula at the university level.